2020
DOI: 10.1148/radiol.2020192855
|View full text |Cite
|
Sign up to set email alerts
|

Breakthrough Hypersensitivity Reactions to Gadolinium-based Contrast Agents and Strategies to Decrease Subsequent Reaction Rates: A Systematic Review and Meta-Analysis

Abstract: EVIDENCE-BASED PRACTICEG adolinium-based contrast agents (GBCAs) have been used clinically for decades and have an excellent safety record (1-3). Immediate hypersensitivity reactions to GB-CAs remain uncommon, estimated by meta-analysis to be approximately nine per 10 000 administrations, with severe reactions occurring in approximately five per 100 000 administrations (4). Limited studies have evaluated repeat GBCA administration in patients with a prior hypersensitivity reaction to a GBCA. The efficacy of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 36 publications
0
32
1
1
Order By: Relevance
“…It does not appear that premedication with corticosteroids prevents a future reaction. A 2019 systematic review and meta-analysis sought patients with immediate reactions to GBCAs who were undergoing repeated administration of GBCAs ( 40 ). The study concluded that in patients with a history of immediate reaction to GBCA, the repeated HRs to the same GBCA may occur in ~39%, despite the use of adequate premedication with corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…It does not appear that premedication with corticosteroids prevents a future reaction. A 2019 systematic review and meta-analysis sought patients with immediate reactions to GBCAs who were undergoing repeated administration of GBCAs ( 40 ). The study concluded that in patients with a history of immediate reaction to GBCA, the repeated HRs to the same GBCA may occur in ~39%, despite the use of adequate premedication with corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of allergic reactions depends on the type of contrast agent used, age, sex and admission status of the patients [13,14]. Patients who have already had allergic reactions to gadolinium (Gd)-based contrast agents are also at high risk (approximately 39 %) for a further allergic reaction with subsequent contrast agent applications, even with drug preparation [15]. Incorrect preparation of the intravenous injection of the contrast agent, which is usually applied by an injector, can lead to incorrect injections outside the vessel (so-called extravasations), the consequences of which can range from temporary pain to necrosis and permanent disability [16].…”
Section: Radiation Protectionmentioning
confidence: 99%
“…Bei Patienten, die bereits allergische Reaktionen auf Gadolinium (Gd) -basierte Kontrastmittel aufwiesen, besteht zudem ein hohes Risiko (ca. 39 %) auf eine weitere allergische Reaktion bei folgenden Kontrastmittelapplikationen, selbst bei medikamentöser Vorbereitung [15]. Eine fehlerhafte Vorbereitung der intravenösen Injektion des in der Regel maschinell applizierten Kontrastmittels kann zu Fehlinjektionen außerhalb des GefĂ€ĂŸes (sog.…”
Section: Risiken Der Mrt Und Kontraindikationenunclassified
“…However, the efficacy of this pretreatment has been questioned because most previous steroid studies have included highosmolarity ICMs that are no longer commonly used in clinical practice and had a higher rate of acute reactions than studies using low-and iso-osmolarity ICMs (4-10) and because previous studies have frequently included both high-risk and average-risk (ie, no previous ICM reaction) patients. Furthermore, breakthrough repeat reactions still occur in patients premedicated with a steroid at a rate of 2%-39% (11)(12)(13). As such, it is unclear whether steroid premedication remains a useful and effective means of preventing repeat allergic-like reactions in high-risk patients.…”
mentioning
confidence: 99%